The evolving role of supreme auditing institutions (SAIs) towards enhancing environmental governance. Issue 1 (2nd January 2021) - Smith, F.H.; Retief, F.P.; Roos, C.; Alberts, R.C.
ABSTRACT: With accelerating environmental degradation, 21st century governments are expected to govern towards more environmentally sustainable outcomes. Supreme Audit Institutions (SAIs) are increasingly recognised as having a key environmental governance role in holding governments to account by expanding their traditional financial audit mandates beyond the oversight of public-sector budgets and accounts to also include environmental aspects. The aim of this paper is to analyse this evolving environmental governance role of SAIs internationally. The methodology relies on the review of relevant literature and results from survey questionnaires obtained from the International Organisation of Supreme Audit Institutions (INTOSAIs) and their Working Groups for Environmental Auditing (WGEAs). The research results show that there is a steady and meaningful increase in opinion that SAIs legislative mandates should make provision for environmental auditing. In practice an increase in environmental-related audits happened in all three spheres of financial-, compliance- and performance auditing, which supports a shift in emphasis from predominantly financial driven audits.